PRESTASI AKADEMIK DITINJAU DARI KETERLIBATAN ORANG TUA DALAM PENDIDIKAN, REGULASI EMOSI DAN HARGA DIRI - , Desma Husni, Dr. Wisnu Martani, Su., Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to study about the correlation between parentsâ involvement in education, emotional regulation, and self-esteem with academic achievement. This research control intelligence in the analysis. Subject of the research are 218 students of VII grade from State Junior High School 6 Yogyakarta. Instruments used to obtain the data are parentsâ involvement scale in education, emotional regulation scale, self-esteem scale and CFIT test. Technique of analysis used regression. The data are about academic achievement obtained from documentation. The result shows: 1) self-esteem significantly effect toward academic achievement (t = 2,287, p < 0,05), 2) parentsâ involvement in education effect does not significance toward academic achievement(t = 1,555, p > 0,05), 3) emotional regulation shows does not significance toward academic achievement (t = 0,468, p > 0,05).